PENGARUH PROGRAM K3 DAN KOMPENSASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. APAC INTI CORPORA BAWEN (STUDI KASUS PADA KARYAWAN BAGIAN WINDING DEPARTEMEN SPINNING 2) - Sihotang, Rita Mustika; Hermani, Agus; Suryoko, Sri (Jurnal Ilmu Administrasi Bisnis, 2015)
This research is motivated that part which plays an important role in achieving the goal of a company is the human resources, namely the employee. Companies can develop better if followed by high employee work productivity. PT. Apac Inti Corpora Bawen has a target to increase employee productivity. However, the production employee winding section spinning department 2 PT. Apac Inti Corpora Bawen in 2013 and 2014 did not meet its targets. The purpose of this study was to determine the influence of HSE programme and compensation either simultaneously or partially on employee productivity spinning department winding section 2. This type of research is "explanatory research". The sampling technique used purposive sampling technique. The sample in this study amounted to 62 employees of the department of spinning winding 2 PT. Apac Inti Corpora Bawen, with the Likert scale measurement. In proving the hypothesis test was used correlation analysis, coefficient of determination test, simple and multiple regression test, and significance test (t test and F test) with SPSS 15.0. The results showed that in partial HSE programme and compensation have positive effect on employee work productivity. HSE programme while simultaneously positive effect on employee work productivity, while compensation has no effect on employee work productivity. Based on the results of the study, the researchers suggest that companies conduct medical examinations to employees with more routine, increase the amount of basic salary and the compensation value compensation beyond salaries, as well as reducing the size of the production targets that have been set to match the capabilities of employees.